Neonatal near miss and the occurrence of negative outcomes in the first year of life: data from a national survey, Nascer no Brasil (Born in Brazil), 2011-2012 - Pauline Lorena Kale; Sandra Costa Fonseca; Silvana Granado Nogueira Gama
Abstract Objectives: estimate the strength of association between neonatal near miss and the nega-tive outcomes in the child's first year of life. Methods: a prospective cohort study on neonatal survivors originating from a national survey "Nascer no Brasil (Born in Brazil), 2011-2012." Main exposure: neonatal near miss (NNM). Negative outcomes: breastfeeding, hospitalization, and post neonatal death (tele-phone interview). For each outcome, the odds ratio (OR) were estimated by univariate (p<0.2) and multivariate (p<0.05) logistic regression models. Results: among 15,675 children 3.3% were neonatal near miss. Neonatal near miss was associated, after adjusting, to: weaning (OR=1.8); hospitalization after hospital discharge (OR=2.2); remained hospitalized (OR=65.6) and post neonatal death (OR=52.4) The increased OR after adjusting revealed negative confounding, such as "remained hospitalized since childbirth" (ORcrude=21.1 and ORadjusted=65.6). Conclusions: although neonatal near miss reflects a good quality of health care, avoiding neonatal death, these survivors have higher risk of negative outcomes in the first year of life.